Learn from the experts. - Allen, Courtney (O'Reilly Media, 2018)
"In this Learn from the Experts interview, Courtney Allen talks to Sri Ray about how BuzzFeed implemented its cloud strategy, including what factors drove the company's decision to adopt cloud computing, the challenges of migrating to the cloud, and what tools his company uses to evaluate, monitor, and manage its cloud-based services, applications, and infrastructure."--Resource description page